2022
DOI: 10.1177/23779608221120506
|View full text |Cite
|
Sign up to set email alerts
|

Nursing and Midwifery Students’ Mental Health Status and Intention to Leave During Covid-19 Pandemic

Abstract: Introduction COVID-19 has not only affected the physical health of people but it has also had a major impact on their mental health. Objective To investigate the nursing, midwifery, and operating room students’ mental health and intention to leave during COVID-19 pandemic. Methods This cross-sectional study was conducted at the nursing and midwifery school of Tabriz, Iran. Over a period of three months (February–May 2021) and through random sampling, 284 students were selected. The research tool consisted of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
2
7
0
1
Order By: Relevance
“…Sedangkan faktor yang dapat mempengaruhi burnout menurut Dos-Santos et al, (2022) adalah semakin professional perawat maka semakin memungkin mengalami gangguan tidur dan burnout dibandingkan dengan asisten perawat. Pada masa pandemic COVID-19 menyebabkan mahsiswa keperawatan mengalami peningkatan stress, kecepasan dan depresi yang mengakibatkan keinginan mahasiswa untuk berhenti dari pendidikan (Haririan et al, 2022).…”
Section: Simpulanunclassified
“…Sedangkan faktor yang dapat mempengaruhi burnout menurut Dos-Santos et al, (2022) adalah semakin professional perawat maka semakin memungkin mengalami gangguan tidur dan burnout dibandingkan dengan asisten perawat. Pada masa pandemic COVID-19 menyebabkan mahsiswa keperawatan mengalami peningkatan stress, kecepasan dan depresi yang mengakibatkan keinginan mahasiswa untuk berhenti dari pendidikan (Haririan et al, 2022).…”
Section: Simpulanunclassified
“…There is also evidence that the lack of team support,55 lack of vocation55 56 or feeling of inadequacy52 increase the turnover likelihood among early-career nurses. Recent international studies have also shown that male nurses report a higher level of intention to leave compared with female nurses 49 51 57…”
Section: Introductionmentioning
confidence: 99%
“…As the future healthcare workforce, trainees are capable and willing to be involved in global health emergencies [9], although the mental health of healthcare trainees has also been impacted during the COVID-19 pandemic [10][11][12][13][14][15][16]. Systematic reviews and metaanalyses found that student nurses reported suffering from fear, stress, anxiety, depression, and sleep disturbance [10,12].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, rates of stress, anxiety and depression are high in medical trainees [13][14][15][16], and some studies identified evidence of suicidal ideation and burnout [17]. The mental health impacts of the pandemic have influenced healthcare trainees' intentions to leave their training [11]. This is not unexpected since systematic reviews show that students and younger age groups are particularly at risk for pandemicrelated distress [2,17], and college/university students more broadly have experienced high rates of anxiety and depression during the pandemic [18][19][20][21][22], often associated with social restrictions and periods of self-isolation [23][24][25].…”
Section: Introductionmentioning
confidence: 99%